2011
DOI: 10.1111/j.1447-0756.2011.01642.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound for evaluation of adnexal malignancy: From 2D to 3D ultrasound

Abstract: Conventional two-dimensional (2D) ultrasound has been widely used for the evaluation of adnexal malignancy in gynecologic fields. This 2D ultrasound evaluation includes a morphological assessment, color/power and pulsed Doppler sonographic assessment, scoring system, and contrast agent assessment of adnexal masses. The introduction of three-dimensional (3D) ultrasound would facilitate the novel assessment of adnexal masses. With the recent advance in 3D power Doppler (3DPD) ultrasound as well as quantitative 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 77 publications
(218 reference statements)
0
12
0
Order By: Relevance
“…"The question raised here is whether or not facial expressions represent a reliable behavior or emotional state, or constitute reflexive behavior on the part of the fetus". 31 Kurjak et al 49 observed that an increase in facial movement is simultaneously associated with a decrease in the number of general movements. This observation is considered to reflect the normal neurological development of the fetus.…”
Section: Late Second and Third Trimestersmentioning
confidence: 99%
See 4 more Smart Citations
“…"The question raised here is whether or not facial expressions represent a reliable behavior or emotional state, or constitute reflexive behavior on the part of the fetus". 31 Kurjak et al 49 observed that an increase in facial movement is simultaneously associated with a decrease in the number of general movements. This observation is considered to reflect the normal neurological development of the fetus.…”
Section: Late Second and Third Trimestersmentioning
confidence: 99%
“…Subsequent to approximately thirty weeks of gestation, there is an increase in long-duration fetal movements, referred to as epochs and episodes". 31 There have been no studies on the comparison of 2D and 4D techniques to assess fetal facial expression or behavior in the late second and third trimesters of pregnancy, in which the neurobehavioral regulations of fetal movement are the most important.…”
Section: Late Second and Third Trimestersmentioning
confidence: 99%
See 3 more Smart Citations